Biological parameters of Luciobarbus callensis populates Beni-Haroun dam, north-eastern Algeria - BERROUK, H; SAHTOUT, F; BOUALLEG, C. (My University, 2020)
Berrouk H, Sahtout F, Boualleg C. 2020. Biological parameters of Luciobarbus callensis populates Beni-Haroun dam, northeastern Algeria. Biodiversitas 21: 5691-5697. Fish age and growth data mainly assist many ichthyologists to understand the life history features of species and populations Growth is a major process of fish biology, and considered as one of the key processes of lengthstructured models of fishes. Thus, the present study was devoted to studying growth of an autochthonous species (Luciobarbus callensis), populating the dam of Beni-Haroun (Mila city, northeast of Algeria), and is known for its socio-economic value and aquaculture interest. The study was conducted on a sample of 257 fish individuals during the period 2015-2016. The age of L. callensis was determined by using the scalimetry method, providing easier sampling and reading procedures, and also high precision. Fish sexes were identified via the observation of gonads, by naked eye based on gonad shape and color, where the number of females was higher (165) than males (92).The obtained results revealed a maximum longevity of seven years of L. callensis, and the determined growth parameters of the separated and combined fish sexes were found to be as follow: L∞ = 47,3 cm; K = 0.29; t0 = -0.51; Ø’ = 2,813 (females); L∞ = 42,11 cm; K = 0.26; t0 = - 0.58; Ø’ = 2,663 (males); and L∞ = 47 37 cm; K = 0.20; t0 = -0.75; Ø’ = 2,652 (combined sex). Moreover, the evolution of the total weight of fishes with respect to their size presents minor allometry (b<3).(with or without sex distinction)